Imam Mahdi in Sunni Tradition: Differences in Beliefs and Interpretations - Nur, Faisal M. (Prodi Studi Agama-Agama, 2023)
The concept of Imam Mahdi holds a special place, but differences in beliefs and interpretations regarding Imam Mahdi within the Sunni community have led to confusion and even disputes among Muslims. To gain a deeper understanding of how Imam Mahdi is viewed from the perspective of Sunni tradition and the differences in beliefs and interpretations, this research will delve into the complexities of these views and identify different frameworks of understanding. This will help us appreciate the diversity of Islamic thought and how these understandings impact religious practices and the perspectives of Muslim communities. Furthermore, it will underscore the importance of inter-sectarian dialogue in today's increasingly complex Muslim society. The research method employed in this study is a literature review, based on the analysis and synthesis of relevant literature on the specific research topic. Titled